PROFILE BENIGN TYPE OF CHRONIC SUPPURATIVE OTITIS MEDIA IN GENERAL HOSPITAL OF THE CHRISTIAN UNIVERSITY OF INDONESIA - Poluan, Fransiskus Harf; Utomo, Bambang Suprayogi Resi; Dharmayanti, Jaene (International Journal of Research -GRANTHAALAYAH, 2021)
Chronic Suppurative Otitis Media (CSOM) Tubotympanic Type is a CSOM without cholesteatoma, limited to the mucosa, and seldom causes complications. According to WHO, the incidence of the CSOM is estimated to be 65 – 330 million worldwide. Prevalence CSOM in Indonesia is 3,9%. According to a survey conducted in 7 provinces in 1996 in Indonesia, most middle ears morbidity is CSOM, especially the CSOM benign type 3%. This study's objective was to identify Profile Benign Type of CSOM at the General Hospital of the Christian University of Indonesia. This study uses a descriptive method and retrospective cross-sectionals. Data retrieval using the secondary database on the patient's medical records. The sample obtained is 60 patients with a total sampling from January 2017 – December 2018. Based on the research result, the highest proportion based on gender is female 33 people (55 %). Based on age, mainly in 55-59 years ten people (16,7 %). Based on the infected ear is right ear 35 people (58,3 %) and based on clinical symptoms, is otorrhea by 46 people (76,7%). Based on risk factor was that there were 53 people (88,3 %) and history of otitis media. Based on the tympanic membrane's perforation, which is a central perforation of 57 people (95 %).